Last acts : the art of dying on the early modern stage - Vinter, Maggie (Magdalena) (Fordham University Press, 2019)
"Last Acts: The Art of Dying on the Early Modern Stage shows how theater reflects, enables, and contests the politicization of life and death. The book analyzes representations of dying in plays by writers including Marlowe, Shakespeare and Jonson, alongside devotional texts and contemporary biopolitical theory"--